Astronomical & Space Science Portal Information System Design for LCRSSS Center in Libya - Benamer, Wisam Hamdi (2009)
The internet technologies are rapidly increasing. The aim of the study is to design and develop an astronomical & space science portal information system (WASSIS). The WASSIS is a real-time application system which provides a convenient graphics user interface (GUI) for both user and Libyan Centre for Remote Sensing and Space Science (LCRSSS) staff. It allows user to make self-registration to become as member of the system, update information, view announcement, view astronomical and space information time-to-time. It also allows administrator to manage user/staff account and view report. All of the services are possible anywhere at any time.